Formulation Tests for The Production of Solid Perfume Based on Patchouli Oil - Maulana, Farid; Amilia, Amilia; Jovial, Citra Aura; Desky, Agil Shaila; Heriana, Nadia; Zakaria, Dhetya Nausa (Journal of Patchouli and Essential Oil Products, 2023)
Perfume is a mixture of essential oils and aroma compounds, fixatives, and solvents used to give fragrance and can be developed as essential oil application products in the form of solid perfume. Solid perfume essential is perfume solid form with advantage that economical, easy to carry, and not easily spilled. Whose main ingredients are from candelilla wax and essential oil. The purpose of this study was to compare the formulation of solid parfume with variations in the addition of heavy fraction patchouli oil which is preferred by the public. The methods used in this study are survey and experimental methods consisting of several stages, namely preformulation, material determination, product manufacture, and product evaluation with several tests. In this research, there were two formulations with the addition of patchouli oil as much as 1 and 3 wt%. The evaluation tests conducted in this study consisted of a hedonic test, a perfume resistance test, an odor acuity test, and an irritation test. The results of this study were that panelists were more interested in F2 which had a longer odor resistance and a higher fragrance intensity.Keywords:patchouli oil, perfume, solid perfume, wax